Novel metal–organic framework biosensing platform for detection of COVID-19 RNA - Aya Elgazar; Rana Sabouni; Mehdi Ghommem; Amin F. Majdalawieh (Scientific Reports)
Abstract The latest pandemic resulting from the novel SARS-CoV-2 coronavirus has significantly affected public health, the worldwide economy, and social life. Metal organic frameworks (MOFs) are currently being implemented in biosensors for rapid and accurate detection of viruses thanks to their exceptional properties. This research aims to develop a Zeolitic Imidazolate Framework-8 (ZIF-8) based fluorescent biosensor for facile and rapid COVID-19 RNA sequence detection. ZIF-8 was characterized using several tests, such as FT-IR, TGA, and PXRD, to examine the MOF’s crystalline structure and thermal stability. The results demonstrated high crystallinity and thermal stability up to a temperature of 550 °C. The experimental study showed that ZIF-8 is an excellent fluorescence quencher, with 78.39% quenching efficiency. Analyzing the adsorption mechanism of probe DNA into ZIF-8 revealed that they can form electrostatic and π–π stacking interactions, forming a P-DNA@ZIF-8 complex and that PET is more dominant than FRET in the quenching mechanism. This ZIF-8 biosensing platform showed high sensitivity towards COVID-19 RNA with an ultra-low limit of detection of 6.24 pM, a rapid detection time of 8 min, and high selectivity to COVID-19 RNA. Indeed, ZIF-8 experienced much lower fluorescence recovery when tested on two mismatched RNAs. The experimental results show the potential use of ZIF-8 as a novel biosensor for a rapid and sensitive COVID-19 diagnosis.